PROFIL LANSIA DI BALI DAN KAITANNYA DENGAN PEMBANGUNAN (Deskripsi berdasarkan hasil Supas 2005 dan Sakernas 2007) - Nyoman Dayuh Rimbawan (PIRAMIDA, 2008)
Discussions about lansia have been increasingly important due to the increasingnumbers of them. This is enabled by the improvement of economic and socialcondition of the society. Lansia is different from other group of people mainly in terms ofhealth and needs aspects.During 1990-2000, lansia has grown 1,8% averagely and during 2000-2005 thegrowth has increased to 2,4% to form more than 311.000 people (9,2 % of population).Description of lansia in Bali is done based on data of Population Census, Supas,and Sakernas. The result shows that most of them are not cost of development, in fact,they are development assets. This can be seen from several indicators, like (1) morethan 80% of lansia has “good” and “fair” health condition; (2) almost 80% of lansia donot need assistance in doing activities; (3) unemployment rate of lansia is very low(<1,0%). Sixty percent of working lansia are employed in agriculture sector, and the restare in trading, hotel& restaurant, and manufacturing industry respectively.